2015
DOI: 10.1128/aac.02347-14
|View full text |Cite
|
Sign up to set email alerts
|

Atovaquone Tolerance in Plasmodium falciparum Parasites Selected for High-Level Resistance to a Dihydroorotate Dehydrogenase Inhibitor

Abstract: Atovaquone is a component of Malarone, a widely prescribed antimalarial combination, that targets malaria respiration. Here we show that parasites with high-level resistance to an inhibitor of dihydroorotate dehydrogenase demonstrate unexpected atovaquone tolerance. Fortunately, the tolerance is diminished with proguanil, the second partner in Malarone. It is important to understand such "genetic cross talk" between respiration and pyrimidine biosynthesis since many antimalarial drug development programs targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Results showed similar nanomolar EC 50 sensitivities of the Dd2, 106/1, 3D7, and HB3 control parasites to ATQ, RYL-552, and CK-2-68. Activities of the Q i antagonist AMA, chloroquine (CQ), and the PfDHODH inhibitor DSM1 were also in the expected ranges for these four controls (31)(32)(33)(34)(35). The clones from the ETC inhibitor-selected lines retained the same CQ responses as those of the original Dd2 (CQ-resistant) and 106/1 (CQ-sensitive) clones ( Table 2).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Results showed similar nanomolar EC 50 sensitivities of the Dd2, 106/1, 3D7, and HB3 control parasites to ATQ, RYL-552, and CK-2-68. Activities of the Q i antagonist AMA, chloroquine (CQ), and the PfDHODH inhibitor DSM1 were also in the expected ranges for these four controls (31)(32)(33)(34)(35). The clones from the ETC inhibitor-selected lines retained the same CQ responses as those of the original Dd2 (CQ-resistant) and 106/1 (CQ-sensitive) clones ( Table 2).…”
Section: Resultsmentioning
confidence: 80%
“…The nuclear pfdhod gene is normally single-copy in P. falciparum but amplification has been found with increases in ATQ EC 50 levels upon DSM1 selection (28,35,38). We tested for pfdhod CNV in the clones listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that proguanil (whose metabolised form cycloguanil, inhibits dihydrofolate reductase) synergises with cytochrome bc1 inhibitors both increasing their potency and abrogating yDHODH-conferred resistance2526. To determine whether our MMV compounds were inhibiting Pf DHODH directly or indirectly by targeting bc1 all the inhibitors were reanalysed in the presence or absence of 1 μM proguanil and the results are summarised in Tables 3 and 4.…”
Section: Resultsmentioning
confidence: 99%
“…The preferable treatment of babesiosis in humans is the combination of atovaquone (AQ) with azithromycin due to their low side effects [4]. Guler et al [5] reported that Plasmodium falciparum rapidly developed resistance to AQ when used as a single drug. Another report showed the relapse of Babesia gibsoni due to the change of amino acid in the mitochondrial cytochrome B that led to a reduction in the efficacy of AQ [6].…”
Section: Introductionmentioning
confidence: 99%